Iterative Approach for Performance Improvement of PLC Systems - Min Hwang, Yu; Ghyu Sun, Young; Sim, Issac; Young Kim, Jin (International Journal of Engineering and Technology, 2018)
In this paper, we propose Turbo equalizer scheme using zero-forcing (ZF) and simulate in power line communication (PLC) systems with high speed. Due to impulsive noise and multipath fading in PLC systems, inter-symbol interference (ISI) happens. We employ Turbo equalizer scheme to get over ISI and improve performance. From simulation results, it is confirmed that the proposed Turbo equalizer can remarkably improve PLC system performance.Â Â
Keywords: Power line communication; multi-path fading; turbo equalizer.